Gender- and sex-sensitive psychopharmacotherapy of alcohol use disorder: a systematic review and meta-analysis protocol - Hiß, Inka Camilla; Hoffmann, Sabine; Reinhard, Iris; Siegmann, Eva-Maria; Bach, Patrick; Kiefer, Falk; Fischer, Ronald; Jäger, Kerstin; Lenz, Bernd (BMJ Open, 2025)
INTRODUCTION: Alcohol use disorder (AUD) is a prevalent, chronic condition generating considerable global morbidity, mortality and socioeconomic burden. Despite the availability of established pharmacotherapies, overall treatment uptake remains low and effect sizes are moderate at best. Emerging evidence highlights substantial differences in treatment response between sexes and genders, yet these factors are rarely systematically considered in clinical trials or routine care. Existing reviews have limited scope and often exclude gender-diverse populations. This project aims to (1) Synthesise evidence on gender- and sex-specific efficacy, safety and adherence in AUD pharmacotherapies, (2) Evaluate the consideration of sex and gender beyond binary classifications in existing research and (3) Develop recommendations for gender- and sex-sensitive treatment strategies. METHODS AND ANALYSIS: A systematic review and meta-analysis will be conducted using (PubMed, Web of Science, Scopus, Google Scholar, German Clinical Trials Register and ClinicalTrials.gov). We will include randomised controlled trials of pharmacotherapies for AUD with a minimum treatment duration of 4 weeks, reporting gender-specific and/or sex-specific results. The literature search will cover studies published up to October 2025, with inclusion restricted to articles published in English or German, regardless of setting. Two reviewers will independently screen records and assess risk of bias (Cochrane RoB), with evidence certainty evaluated using Grading of Recommendations Assessment, Development and Evaluation and aligned to Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 and Sex and Gender Equity in Research guidelines. ETHICS AND DISSEMINATION: Ethics approval is not required as only data from already completed studies and supplementary information directly provided by study authors are used. Findings and recommendations will be disseminated in peer-reviewed journals and presented at conferences and workshops. PROSPERO REGISTRATION NUMBER: CRD420251079160.
CRIS-Team Scopus Importer:2025-12-12
Keywords: CLINICAL PHARMACOLOGY; Drug Therapy; Meta-Analysis; Sexual and Gender Minorities; Substance misuse; Systematic Review